Validation of a Scale to evaluate Pathological Digital Game Dependence - King,Anna Lucia Spear (2019)
BACKGROUND INFORMATION: Digital game or video game disorders have been recently (June 2018) included in ICD-11 (International Classification of Diseases) by the World Health Organization (WHO). The disorder can occur with or without an internet connection. OBJECTIVE: Validation of a scale to evaluate the dependence of pathological digital game (PDGD). METHOD: Validation of the PDGD was performed in 5 phases: (1) initial scale construction with 20 questions, (2) expert assessment, (3) application to 200 volunteers, (4) statistical analysis and production of results using statistical programs, (5) elaboration of the final validated scale. RESULTS: We used the R statistical program Version 3.4.2 and the “dplyr” package to present the descriptive statistics, the hypotheses tests of differences of means and the factorial analysis. The last step was to calculate Cronbach’s alpha, in order to measure the internal consistency of the questionnaire. The value found was 0.955, which is very good. CONCLUSIONS: This research allowed us to construct a final version of the PDGD suitable for the clinical contexts and usable in research on the dependence of digital games. This scale may contribute to future studies, conscious use of technologies, reduction of physical and emotional damage and improvement of the quality of life.